La presencia estética y discursiva de la televisión en el cine de Pedro Almodóvar - Iturbe Tolosa, Andoni (Fonseca, Journal of Communication, 2020)
This article is focused on the regular and constant presence of TV in Pedro Almodóvar’s movies. Television, starting from Almodóvar´s first film (Pepi, Luci, Bon y otras chicas del montón, 1980), acquires relevance that will be the object of study from a discursive and aesthetic point of view. The methodology consists in the bibliographic research and the analysis of the scripts, drafts, press kits and films. Kika (1993) is not the only film by Pedro Almodóvar where TV is implanted. Quite on the contrary, we shall see that the TV set has practically a constant presence in Almodóvar’s oeuvre. As a result, it is important to mention the object value of the TV screen and the bodily position in front of the TV set. Furthermore, we will underline an itinerary on the discourses on television in the filmography of Almodóvar.